2011
DOI: 10.1111/j.1439-037x.2011.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid Activates Antioxidative Defence System and Seedling Growth in Brassica napus L. under Water-Deficit Stress

Abstract: The present study assesses the effects of 5‐aminolevulinic acid (ALA, 0, 0.1, 1 and 10 mg l−1) on the growth of oilseed rape (Brassica napus L. cv. ZS758) seedlings under water‐deficit stress induced by polyethylene glycol (PEG 6000, 0 and −0.3 MPa). Water‐deficit stress imposed negative effects on seedling growth by reducing shoot biomass, cotyledon water potential, chlorophyll content and non‐enzymatic antioxidants (glutathione and ascorbic acid) levels. On the other hand, water‐deficit stress enhanced the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 56 publications
4
60
0
Order By: Relevance
“…The compound presumably promoted the chilling tolerance effect in plants under low-light which suppressed respiration (Hotta et al, 1998;Wang et al, 2004), and improved tolerance to salinity stresses (Nishihara et al, 2003). ALA not only promotes the growth and yield of crop plants, but also acts as an alleviator of oxidative damage and enhances the activity of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), and ascorbate peroxidase (APX) to encounter radicals under stress conditions i.e., drought stress and NaCl stress (Nishihara et al, 2003;Li et al, 2011;Liu et al, 2011). Korkmaz and Korkmaz (2009) proposed that seed priming with ALA enhanced the germination rate of pepper seedlings under chilling stress, and improves germination, and seedling uniformity, especially under unfavorable environmental conditions.…”
mentioning
confidence: 99%
“…The compound presumably promoted the chilling tolerance effect in plants under low-light which suppressed respiration (Hotta et al, 1998;Wang et al, 2004), and improved tolerance to salinity stresses (Nishihara et al, 2003). ALA not only promotes the growth and yield of crop plants, but also acts as an alleviator of oxidative damage and enhances the activity of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), and ascorbate peroxidase (APX) to encounter radicals under stress conditions i.e., drought stress and NaCl stress (Nishihara et al, 2003;Li et al, 2011;Liu et al, 2011). Korkmaz and Korkmaz (2009) proposed that seed priming with ALA enhanced the germination rate of pepper seedlings under chilling stress, and improves germination, and seedling uniformity, especially under unfavorable environmental conditions.…”
mentioning
confidence: 99%
“…Xu et al (2010) suggested that ALA at low concentrations could increase the growth of kudzu Pueraria phaseoloides) by increasing photosynthetic rate. Previous studies have shown that low concentrations of exogenous ALA promote plant growth, development, and responses to environmental stresses (Bindu and Vivekanandan, 1998), such as crop productivity (Hotta et al, 1997a) and stress tolerance (Hotta et al, 1998;Watanabe et al, 2000;Wang et al, 2004;Sun et al, 2009;Liu et al, 2011;Naeem et al, 2011). These previous studies suggest that the effect of ALA on plants depends on the concentration of ALA. ALA at low concentrations is known to promote growth and development of some plants, animals, algae and photosynthetic bacteria (Chakraborty and Tripathy, 1990;Balestrasse et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…These results suggest that Sal and AgNPs lead to a condition of oxidative stress in cells, which may arise due to the imbalance of oxidant and antioxidant levels in cells. 78 Overall, oxidative stress was induced by the treatment of Sal and AgNPs as confirmed by the significant decrease in GSH, SOD, and CAT levels in the treated groups.…”
mentioning
confidence: 80%